2009
DOI: 10.1016/j.ijgo.2008.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visceral peritoneal closure on scar formation at cesarean delivery

Abstract: Closure of the visceral peritoneum at cesarean delivery may produce an inflammatory reaction and adhesions, evidenced by reactive and regenerative mesothelial hyperplasia and submesothelial fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 20 publications
0
23
0
2
Order By: Relevance
“…Besides studies listed on Table 1, all adhesion scoring systems were non-site-specific or unclearly described [13][14][15][16][17][18]. There were three randomized studies (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides studies listed on Table 1, all adhesion scoring systems were non-site-specific or unclearly described [13][14][15][16][17][18]. There were three randomized studies (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Komoto et al evaluated the frequency of adhesions but not the severity [15]. Malvasi et al evaluated adhesions in limited locations, primarily between the bladder and the uterus, and severity of adhesions was graded as none, mild, or severe [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…86 However, studies on this subject have concluded that insufficient data are available to make a pronouncement on the issue and that adequately powered and appropriately designed trials are needed. 87,88 A recent study by Malvasi and colleagues 89 supports nonclosure of the visceral peritoneum for CD. These authors performed light microscopy and scanning electron microscopy on specimens obtained from patients having a repeat CD following nonclosure and closure of the peritoneum in their first CD.…”
Section: Closure and Nonclosure Of The Visceral And Parietal Peritoneummentioning
confidence: 92%
“…The longterm follow-up showed no differences in pain, fertility, urinary symptoms, and adhesions [38,44,45]. It is proven that closure of the visceral peritoneum at cesarean delivery may produce an inflammatory reaction and adhesions, caused by reactive and regenerative mesothelial hyperplasia and submesothelial fibrosis [33].…”
Section: Expansion Of Uterine Incisionmentioning
confidence: 99%